2007 IEEE International Conference on Communications 2007
DOI: 10.1109/icc.2007.851
|View full text |Cite
|
Sign up to set email alerts
|

WiMAX Downlink OFDMA Burst Placement for Optimized Receiver Duty-Cycling

Abstract: Mobile wireless broadband access networks are now becoming a reality, thanks to the emerging IEEE 802.16e standard. This kind of network offers different challenges when compared to the fixed ones, as power consumption becomes a major concern. In this standard, a strict organization of the downlink bursts is not guaranteed in the OFDMA frame and this may lead to extra power consumption for the receiver, decreasing the device's lifetime. In the present paper, we introduce an optimization algorithm capable of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 4 publications
0
26
0
1
Order By: Relevance
“…As the DL-MAP is broadcasted to all SSs, minimizing its size will also reduce the awake period of every SS. Some algorithms [6] specifically deal with this goal, as we will see in Section 2.3.…”
Section: Quality Of Service Fulfillmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As the DL-MAP is broadcasted to all SSs, minimizing its size will also reduce the awake period of every SS. Some algorithms [6] specifically deal with this goal, as we will see in Section 2.3.…”
Section: Quality Of Service Fulfillmentmentioning
confidence: 99%
“…In [6], authors seek to optimize the receiver awake cycle by reducing the average duration and delay of the bursts within a given frame. Although this is an important goal for a resource allocator as stated in Section 2.2, the algorithm uses a full search approach, making it impractical for more than eight users.…”
Section: Related Workmentioning
confidence: 99%
“…Claude Desset and his colleges [5] showed that only 8 users at a maximum can be supported with a binary-tree full search algorithm for burst mapping in a rectangular shape. However, this work does not consider the variations of possible mapping pairs for each particular burst.…”
Section: Design Factorsmentioning
confidence: 99%
“…In this example, we try all possible widths (from 2 to 12) resulting in 2×19, 3×13, 4×10, 5×8, 6×7, 7×6, 8×5, 9×5, 10×4, 11×4, 12×4. These mappings will result in the over allocation of 1,2,3,3,5,5,3,8,3,7, and 11, respectively. The constraints of the maximum allowable width and height still apply.…”
Section: A Algorithm Descriptionmentioning
confidence: 99%
“…This violates our goal of minimizing burst overhead. The binary-tree full search can support only 8 subscribers [13] and so it is not of any practical use.…”
Section: Wimax Frame Structurementioning
confidence: 99%